Review of the dietetic and MDT management of Cystic Fibrosis (UCC Student Medical Journal, 2024)
INTRODUCTION: Cystic Fibrosis (CF) is an autosomal recessive disorder due to mutations in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene leading to abnormality of chloride channels in mucus and sweat producing cells. The respiratorysystem (lungs) and digestive system (GIT) are primarily impacted, leading to life threatening complications (Rafeeq and Murad, 2017). Ireland has the highest incidence of CF in the world. Approximately 1 in 19 Irish people are said to 'carry' one copy of the altered gene that causes CF (Cystic Fibrosis Ireland, 2023). More than 1900 mutations of CF have been identified (Rafeeq and Murad, 2017).METHODS: Articles for review were sourced from the academic database PubMed. Results were screened using PICOS criteria, focusing on dietetic management of CF. Papers dating back as far as the 1980’s were included in the review due to their continuing relevance in CF treatment today.RESULTS: Initial database searches identified 61 results, which were then screened for relevance to the objectives of this review. Treatment of CF requires a multi-disciplinary team approach, for which Nutrition and Dietetic management is integral. Lifelong management of CF includes pharmaceutical treatment to manage symptoms, case specific diet and lifestyletherapy, management of complications and co-morbidities, and novel therapies such as CFTR modulators.CONCLUSION: The identification of the faulty CFTR gene that causes CF was an important step in managing the disorder, yet has not led to a cure for the condition. Life expectancy for patients with CF has steadily improved during the last three decades, with medicalmanagement of symptoms and advances in CF therapies. Complications associated with the condition are treated on a case-by-case basis due to complexity of symptoms and individuality of the condition. Dietetic management includes a high calorie, high salt, and high protein diet and routine monitoring for changes in symptoms and nutritional deficiencies.
Keywords: Cystic Fibrosis; dietetic management; CFTR gene; physical activity in cystic fibrosis; prevalence of cystic fibrosis in Ireland